The Role of Creative and Interactive Methods in Teaching Pencil Drawing in Higher Pedagogical Education - Sa’diyev Soli Tolipovich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the role of creative and interactive methods in teaching pencil drawing in higher pedagogical education. The study highlights how project-based learning, group work, problem-based tasks, and the “Flipped Classroom” approach enhance students’ artistic thinking, independent reasoning, and creative potential. The integration of digital technologies and interdisciplinary approaches in art education is also discussed as a means to develop students’ professional competencies and aesthetic perception.